The effects of apixaban on clot characteristics in atrial fibrillation: A novel pharmacodynamic biomarker. Issue 2 (26th March 2022) - Lawrence, Matthew J.; Evans, Vanessa; Whitley, Janet; Pillai, Suresh; Williams, Phylip R.; Coulson, James; Krishnan, Manju; Slade, Peter; Power, Kieron; Morris, Roger H.K.; Evans, Phillip A.
Abstract: Atrial fibrillation (AF) is a major risk factor for stroke. We aim to characterize AF patients and the effects of apixaban therapy in terms of clot microstructure using gel point analysis, a novel biomarker. Seventy‐eight patients were included in the study, 50 Stroke with AF (AF‐S), and 28 AF without stroke (AF). Pre‐ and post‐anticoagulation samples were collected: gel point (GP) analysis was performed to obtain (i) TGP (the time taken to reach the GP or the clot formation time) and (ii) df, the fractal dimension of the clot, a quantification of clot fibrin microstructure at the GP. At baseline, the AF‐S group had a df  = 1.70 (±0.05) and TGP = 306 (±73 s). The AF group had a df = 1.70 ± 0.05 and TGP = 346 ± 78 s, showing a significantly shortened TGP in the stroke group ( p  = .008). For both groups, apixaban significantly prolonged TGP, p  = .005, but resulted in no change in df. Apixaban prolonged clotting time while having no significant impact on the blood's ability to form stable clots (no change in df ). This indicates that apixaban provides protection from the formation of thrombi by reducing clotting kinetics.